Conserving Certainty of Crypto Transactions with Machine Learning Methodologies - S. Haripriya,; Dr. D. Banumathy,; Dr. A. Jeyamurugan,; Dr. G. Madasamyraja, (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
Nowadays there are increase in fraudulent activities within cryptocurrencies transactions. To combat this, we propose a novel framework that integrates machine learning methodologies with the SHA-256 algorithm to enhance security and predict price fluctuations. This framework aims to provide a comprehensive solution for preventing fraudulent activities in cryptocurrencies transactions contributing to a more secure.
Keywords: Cryptocurrencies Transactions; Preventing Fradulent Activities; Future Prediction